Effects of word frequency and spelling-to-sound regularity in naming with and without preceding lexical decision. - Hino, Yasushi; Lupker, Stephen J. (Journal of Experimental Psychology. Human Perception & Performance, 2000)
The effects of word frequency and spelling-to-sound regularity were examined using standard naming, standard lexical-decision, go/no-go naming, and go/no-go lexical-decision tasks. In both the standard and go/no-go naming tasks, tasks requiring phonological coding, a significant Frequency×Regularity interaction was observed. That is, the regularity effect was limited to low-frequency words. In the standard and go/no-go lexical-decision tasks, tasks not requiring phonological coding, no Frequency×Regularity interaction was observed. These results indicate not only that the Frequency×Regularity interaction is a product of phonological coding processes but also that these processes are similar in the standard and go/no-go naming tasks. Results are discussed in terms of the dual-route and the parallel distributed processing frameworks. Reprinted by permission of the publisher.